Influence of initial stresses and unloading rates on the deformation and failure mechanism of Jinping marble under true triaxial compression. (May 2019) - Xu, Hong; Feng, Xia-Ting; Yang, Chengxiang; Zhang, Xiwei; Zhou, Yangyi; Wang, Zhaofeng
Abstract: To investigate the deformation and failure mechanism of rock influenced by initial stress and unloading rates, this study presents minimum principal stress unloading tests of Jinping marble under true triaxial compression conditions under various initial stresses and unloading rates based on the in situ stresses measured in the China Jinping Underground Laboratory Phase II (CJPL-II). The effects of initial stresses and unloading rates on the bearing capacity and the deformation and failure characteristics of Jinping marble were analysed. The relationship between the strains in the three principal stress directions and the unloading extent of σ 3 is defined using parameters such as the strain-unloading extent ratio and the unloading strain rate. With an increase in the initial σ 1, the increase in strain-unloading extent ratio and unloading strain rate changed from linear to exponential earlier, and sample failure occurred with a smaller unloading extent. Meanwhile, the number of acoustic emission rings and the amount of cumulative energy increased, and the sample failure changed from tensile failure to a mixture of tensile and shear failure that showed more transgranular cracks in the microscopic images. With an increase in the initial σ 2 or σ 3, the overall trend of the failure characteristics was similar to that with an increase in the initial σ 1, but the sample failed with a larger unloading extent, and the increase in strain-unloading extent ratio and unloading strain rate changed from linear to exponential later. The influence of unloading strain rate shows that as unloading strain rate increased, the sample failed with a larger unloading extent and changed from a mixture of tensile and shear to tensile failure, and more transgranular cracks were observed in the microscopic images. Highlights: σ 3 unloading tests with different unloading rates and initial stress levels under true triaxial stresses were carried out. The bearing capacity, deformation process, and failure mode of Jinping marble under σ 3 unloading condition were examined. The relationships between strains along principal stress directions and unloading extent of σ 3 ( Δσ 3 ) were established. Failure mechanisms of Jinping marble were identified based on AE data and SEM pictures of fractures.